Computing Our Way to Paradise?: The Role of Internet and Communication Technologies in Sustainable Consumption and Globalization - Rattle, Robert (Rowman & Littlefield Publishers, 2010)
Rattle's new book challenges key assumptions concerning the role of Internet and communication technologies (ICTs) in globalization processes. The author argues that while globalization is predicated upon a strong, extensive, and interconnected global ICT network of products, processes, and services, the real environmental and health benefits remain far from certain. ICTs have been promoted as the next economic wave with the potential to generate jobs, wealth, and prosperity to surpass that of the industrial era. It is assumed the environmental impacts will be negligible or even beneficial in this shift towards a service economy. Rattle investigates these current and expected trends in ICTs and their potential contribution to sustainable development. His book is an indispensable overview for researchers and instructors in globalization, Internet communication technologies, and environmental anthropology or sociology, as well as a resource for policy makers in environmental protection, sustainable development, sustainable consumption, and the social role of science and technology.